HEALTH INFORMATION SYSTEMS SUPPORTED BY MOBILE TECHNOLOGIES: : A NEW TREND - Cristina Ribeiro Akamine, Suellen (Health and Society, 2021)
Information systems have been standing out and constantly evolving due to changes and the economic impact they produce on organizations and society, and also due to the evolution of information technology itself. These systems are made up of a structure capable of guaranteeing the collection and transformation of data into information, and the involvement of professionals in processes of selection, collection, classification, storage, analysis, dissemination and data retrieval is essential. Mobile technologies offer support so that information systems can be implemented and used more efficiently and quickly, but there are many obstacles, such as the unavailability of technological resources by a large part of the population, difficulties in accessing and connecting, among others. The methodology used to carry out this study was the bibliographical research through literature analysis of scientific articles and other texts. It was concluded that health information systems and mobile technologies tend to conquer more space each day, as they provide more agility and quality in health services, but it is still necessary to improve the population's access to these technological resources.